Screening for kidney disease in children on World Kidney Day in Lagos State, Nigeria - Solarin, Adaobi U; Madise-Wobo, Akpoembele D; Awobusoyi, Olugbenga; Umezudike, Theophilus I; Onyido, Okwuchi E; Amisu, Mumuni; Gbelee, Olusegun H; Animashaun, Barakat A (African Journal of Nephrology, 2018)
Background: Across the world, World Kidney Day (WKD) is marked yearly to increase awareness of kidney diseases. In 2016, its focus was on children for the first time. We report on a WKD screening initiative for kidney disease that was conducted in two public schools in Lagos State, Nigeria. Methods: Participants were recruited after guardians provided signed consent and older children gave assent. Baseline data were obtained which included family history of chronic diseases like sickle cell disease, hypertension, diabetes, renal disease, and the use of herbal medications. Anthropometric parameters such as height, weight and body mass index (BMI) were recorded. Investigations included urinalysis, measurement of serum creatinine and estimation of glomerular filtration rate (eGFR) using the Schwartz formula. Results: A total of 405 children were screened; there were 190 (46.9%) males and 215 females. The children were aged 2 to 17 years with a mean age of 9.1 ± 3.0 years. Over 80% of the children had normal nutritional status. Severe thinness was seen in 22 (6.8%) whereas overweight was present in 10 (3.1%). Only 1 was obese. eGFR was above 90 mL/min/1.73 m2 in 232 (94.3%) of the participants. Hypertension was present in 47 (14.4%), with the highest rate among those 0–8 years old. Proteinuria was detected in 118 (29.2%); none of the children had haematuria. Systolic hypertension, a family history of smoking and the use of herbal medications were associated with proteinuria. Conclusions: The study has highlighted a high rate of proteinuria, associated with the use of herbal medications, hypertension and a family history of smoking. Screening for renal disease in children with appropriate follow-up and timely intervention to avoid progression to end-stage renal disease is imperative.